Total synthesis and determination of relative and absolute configuration of multiplolide A - Ramana, C. V.; Khaladkar, Tushar P.; Chatterjee, Soumitra; Gurjar, Mukund K. (Journal of Organic Chemistry, 2008)
A flexible approach for total syntheses of possible multiplolide A diastereomers establishing the relative and absolute configuration is documented. The adopted strategy features ring-closing metathesis (RCM) as the key reaction and screening of a set of substrates for the feasibility of RCM in general and for the requisite E-configuration of ring olefin in particular. Selective protecting groups manipulation prior to the assembly of the central macrocyclic core was instrumental in installing the epoxide functionality on a fully deprotected nonenolide at the end of the synthesis.